Analysis of the distribution and scholarly output from National Institute of Academic Anaesthesia (NIAA) research grants. (30th March 2018) - El‐Boghdadly, K.; Docherty, A. B.; Klein, A. A.
Summary: The National Institute of Academic Anaesthesia (NIAA) was founded in 2008 to lead a UK strategy for developing academic anaesthesia. We aimed to assess the distribution of applications and quantify the academic returns of NIAA‐supported research grants, as this has hitherto not been analysed. We sought data on the baseline characteristics of all grant applicants and recipients. Every grant recipient from 2008 to 2015 was contacted to ascertain the status of their supported research projects. We also examined Google Scholar, Scopus ® database and InCites Journal Citation Reports for citation, author and journal metrics, respectively. In total, 495 research project applications were made, with 150 grants being awarded. Data on 121 out of 150 (80.7%) grant awards, accounting for £3.5 million, were collected, of which 91 completed studies resulted in 140 publications and 2759 citations. The median (IQR [range]) time to first or only publication was 3 (2–4 [0–9]) years. The overall cost per publication was £14, 970 (£7457–£24, 998 [£2212–£73, 755]) and the cost per citation was £1515 (£323–£3785 [£70–£36, 182]), with 1 (0–2 [0–8]) publication and 4 (0–25 [0–265]) citations resulting per grant. The impact factor of journals in which publications arose was 4.7 (2.5–6.2 [0–47.8]), with the highest impact arising from clinical and basic science studies, particularly in the fields of pain and peri‐operative medicine. Grants were most frequently awarded to clinical and basic science categories of study, but in terms of specialty, critical care medicine and peri‐operative medicine received the greatest number of grants. Superficially, there seemed a geographical disparity, with 123 (82%) grants being awarded to researchers in England, London receiving 48 (32%) of these. However, this was in proportion to the number of grant applications received by country or city of application, such that there was no significant difference in overall success rates. There was no significant difference in productivity in terms of publications and citations from grants awarded to each city. The 150 grants were awarded to 107 recipients (identified as the most senior applicant for each grant), 27 of whom received ≥ two grants. Recipients had a median career total of 21 (8–76 [0–254]) publications and 302 (44–1320 [0–8167]) citations, with an h‐index of 8 (3–22 [0–54]). We conclude that a key determinant of grant success is simply applying. This is the first study to report the distribution and scholarly output of individual anaesthesia research grants, particularly from a collaborative body such as the NIAA, and can be used as a benchmark to further develop academic anaesthesia in the UK and beyond.